Benefit of STR-based chimerism analysis to identify TA-GVHD as a cause of death: Utility of various biological specimens. (April 2016) - Raina, Anupuma; Chaudhary, Garima; Dogra, Tirath Das; Khandelwal, Deepchand; Balayan, Ajay; Jain, Vandana; Kanga, Uma; Seth, Tulika
Transfusion-associated graft-versus-host disease (TA-GVHD) is a rare condition. It can occur after blood transfusion in immune-compromised and occasionally even in immune-competent patients, and is associated with a mortality rate of >90%. The diagnosis of TA-GVHD is often delayed because of its non-specific clinical features. A case of an immune-competent child who developed TA-GVHD is reported here. DNA profiling (short tandem repeat analysis), a technique that has a wide application in forensic medicine, was performed to detect the presence of donor cells in this patient. The findings suggest that more studies are needed with this tool, and the diagnostic potential of using other multiple biological specimens for DNA profiling such as the hair follicle and buccal swab should be evaluated. This is the first case report where the donor's DNA fingerprinting pattern was substantiated from a patient's hair follicle sample. Chimerism was also present in the blood and buccal swab specimens.